2019
DOI: 10.1109/access.2019.2923275
|View full text |Cite
|
Sign up to set email alerts
|

Halal Products on Twitter: Data Extraction and Sentiment Analysis Using Stack of Deep Learning Algorithms

Abstract: Twitter is a leading platform among social media networks. It allows microblogging of up to 140 characters for a single post. Owing to this characteristic, it is popular among users. People tweet about various topics from daily life events to major incidents. Given the influence of this social media platform, the analysis of Twitter contents has become a research area as it gives us useful insights on a topic. Hence, this paper will describe how Twitter data are extracted, and the sentiment of the tweets on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 9 publications
0
49
0
2
Order By: Relevance
“…In the literature, several works have been developed to manage Twitter data [6] [7], but the most part of them focuses on solving the event detection problem [1] [18], whereas, to the best of our knowledge, only recently researches are devoted to geo-locate Twitter events [2].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, several works have been developed to manage Twitter data [6] [7], but the most part of them focuses on solving the event detection problem [1] [18], whereas, to the best of our knowledge, only recently researches are devoted to geo-locate Twitter events [2].…”
Section: Related Workmentioning
confidence: 99%
“…Once computed the set of candidate location names, it uses the Google Maps API 6 to verify whether the candidate location names correspond to effective locations. In particular, for each candidate location name, the Google Maps API verifies whether there exists an exact, partial or null match with real locations.…”
Section: F Candidate Location Computationmentioning
confidence: 99%
“…In a research [27] that focused on tweets of two halal products, i.e., halal tourism and halal cosmetics, twitter data over a span of 10 years were extracted using the twitter search function, and an algorithm to filter the data. Later, DL algorithm was used to calculate and analyze the tweet's sentiments.…”
Section: Related Workmentioning
confidence: 99%
“…The outcomes concluded that the introduced approaches were evaluated and demonstrated that the approaches outperformed other baselines where the performance of task of aspect OTE was enhanced with 39% while the second task had shown the enhancement of 6% in the performance. Then, in 2019, stack of deep learning algorithms was proffered by Feizollah et al [23] for analyzing the sentiments. The author performed analysis on the tweets on Halal products which were, Halal cosmetics and Halal tourism.…”
Section: Related Workmentioning
confidence: 99%